Recentering the Borderlands: Matepe as Sacred Technology from the Mutapa State to the Age of Vapostori - Mory, Jocelyn Aimee (My University, 2021)
Decolonial scholars insist that the work of decolonization must, at its core, involve understanding and dismantling the Western epistemologies that shape knowledge production in the academy. Historian Mhoze Chikowero identifies a particular scarcity narrative that is rooted in colonial sound archives and permeates current scholarship on African music (2015). His research, along with works by Andrew Mark (2017), shows how this scarcity narrative depicts Zimbabwean music in a state of constant decline and in need of “rescuing” by foreign NGOs and academics, thereby perpetuating foreign control over indigenous cultural property. In this dissertation I respond to Chikowero and Mark’s critical analyses of the scarcity narrative through a case study of matepe, a marginalized music tradition from the northeastern borderlands of Zimbabwe and central Mozambique. I provide a nuanced historical account of matepe music cultures that centers localized understandings of music sustainability and cultural adaptation based on archival, ethnographic, and applied methodologies. The main framework of this dissertation is based on the Nyahuna prophecy, a locally-specific prediction of cultural decline and recovery in northeastern Zimbabwe that was delivered by Nyahuna, a prominent mhondoro (clan) spirit of the Marembe people in 1958. Through his spirit medium, Nyahuna predicted that the Marembe people would go through a period of time in which their cultural traditions would be suppressed – first by war, then by evil spirits, and finally by the growth of independent Apostolic churches, or Vapostori. Within each of these time periods I offer historical and ethnographic accounts that detail the ways in which matepe musicians have adapted their practices to changing economic, political and religious landscapes. Ultimately, within the current time period, I argue that musicians actively work towards recontextualizing matepe music to reduce the stigma of the instrument’s spiritual associations without desacralizing it. This recontextualization provides avenues for culture bearers to learn the sounds of matepe music within a predominantly Christian community. My dissertation research was a multi-year, collaborative project that included the repatriation of over 150 music recordings and 250 photographs of matepe music from the International Library of African Music (ILAM) at Rhodes University in Grahamstown, South Africa. The unpublished archival collections are from the works of Hugh and Andrew Tracey, who recorded matepe music from 1933 to the mid-1990s, during periods of significant political and social upheaval. The archival collections provide a means to address the lack of music scholarship on marginalized ethnic communities in Zimbabwe. This dissertation also builds upon existing anthropological and historical research of southeastern Africa in a way that centers the significance of traditional African music.
Thesis (Ph.D.)--University of Washington, 2021
Keywords: Archives; Ethnomusicology; Mbira; Repatriation; Zimbabwe; Music; Music history; Music